DETERMINAN INISIASI MENYUSU DINI (IMD) WANITA USIA 15-49 TAHUN DI INDONESIA (ANALISIS DATA SDKI 2012) - Nur Aini; Budyanra Budyanra; Indonesian Journal of Statistics and Its Applications IJSA (Indonesian Journal of Statistics and Applications, 2019)
Early Breastfeeding Initiation (EBI) is one of the most effective ways to reduce neonatal mortality in Indonesia. Implementation of EBI in Indonesia in 2012 is still in the "adequate" category according to World Health Organization (WHO) and is in "less" category according to International Baby Food Action Network (IBFAN). Implementation of EBI in Indonesia is still under other ASEAN Association countries such as Philippines, Cambodia and Myanmar. The low application of the EBI is thought to be influenced by maternal factors as well as environmental factors. This study aims to determine the factors that affect the status of EBI in Indonesia and see a general description of the status of EBI based on its characteristics. The data used are raw data of IDHS 2012 and analyzed using logistic regression model of proportional partial ordinal odds. The results obtained are the variables of antenatal care visit, maternal working status, place of residence, place of delivery, method of delivery, and parity are determinant of EBI status in Indonesia.